The Inari Saami Wikipedia - Brecciaroli, Fabrizio (Septentrio Conference Series, 2021)
The Inari Saami traditionally inhabit the area around Lake Inari in northern Finland. Despite being a minority group among the Saami, the Inari Saami have distinctive cultural traits as well as their own language, which has now about 400–450 speakers, including many children. This makes it a small language community in Wikipedia terms. It is still worth noting that Inari Saami is one of the most successful revitalisation processes in the world. During the last decades the language community has organised language nests for Inari Saami children, and it has taught the language to key members of the middle generation. The third phase of the revitalisation, strengthening the literacy of the language, is now in its initial phase. And this is where Wikipedia comes into play. In my presentation I am going to illustrate how the Inari Saami Wikipedia was born and what were the steps taken by the Inari Saami Language Association to make it all happen. I will also explain how we currently encourage the community to take an active role in developing the Inari Saami Wikipedia. We try to involve people from different backgrounds, but our main focus is on young people and students who can write Wikipedia articles as part of their studies at the University of Oulu and at the Sámi Education Institute (SAKK) in Inari. The ultimate goal is to create content that caters to the needs of the Inari Saami school in Inari and to give schoolchildren the possibility to use Wikipedia in their own language as a resource for assignments and classwork.